2022
DOI: 10.15420/ecr.2021.52
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in Chronic Kidney Disease

Abstract: Arrhythmias cause disability and an increased risk of premature death in the general population but far more so in patients with renal failure. The association between the cardiac and renal systems is complex and derives in part from common causality of renal and myocardial injury from conditions including hypertension and diabetes. In many cases, there is a causal relationship, with renal dysfunction promoting arrhythmias and arrhythmias exacerbating renal dysfunction. In this review, the authors expand on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Patients with CKD are vulnerable to cardiac arrhythmia and in many cases, renal dysfunction stimulates arrhythmia and arrhythmia exacerbates renal dysfunction [ 2 ]. In a recent study, the ARIC study, a 2-week cardiac monitoring of patients with CKD revealed a high prevalence of non-sustained ventricular tachycardia (30.2%) and AF (7.4%), while ventricular ectopy was present in more than 90% of patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with CKD are vulnerable to cardiac arrhythmia and in many cases, renal dysfunction stimulates arrhythmia and arrhythmia exacerbates renal dysfunction [ 2 ]. In a recent study, the ARIC study, a 2-week cardiac monitoring of patients with CKD revealed a high prevalence of non-sustained ventricular tachycardia (30.2%) and AF (7.4%), while ventricular ectopy was present in more than 90% of patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the ARIC study, a 2-week cardiac monitoring of patients with CKD revealed a high prevalence of non-sustained ventricular tachycardia (30.2%) and AF (7.4%), while ventricular ectopy was present in more than 90% of patients [ 13 ]. The mechanism of arrhythmia in CKD may be due to electrolyte disturbances and/or the damage caused to kidneys and heart tissues by common comorbidities like hypertension and diabetes mellitus [ 2 ]. Arrhythmia causes premature death in the general population as well as in patients with CKD [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations